2004
DOI: 10.1002/mrc.1439
|View full text |Cite
|
Sign up to set email alerts
|

103Rh NMR spectroscopy and its application to rhodium chemistry

Abstract: Rhodium is used for a number of large processes that rely on homogeneous rhodium-catalyzed reactions, for instance rhodium-catalyzed hydroformylation of alkenes, carbonylation of methanol to acetic acid and hydrodesulfurization of thiophene derivatives (in crude oil). Many laboratory applications in organometallic chemistry and catalysis involve organorhodium chemistry and a wealth of rhodium coordination compounds is known. For these and other areas, 103Rh NMR spectroscopy appears to be a very useful analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 108 publications
4
28
0
Order By: Relevance
“…[8] Given the advances in high-field NMR and the development of reverse detection methods, acquisition of NMR data of the so-called low-γ nuclei has been greatly facilitated. This is peculiarly true for 103 Rh NMR where improvement in NMR probe and detection field has allowed a better comprehension [9] of the 103 Rh chemical shifts. A pioneer in this field is von Philipsborn.…”
Section: Introductionmentioning
confidence: 93%
“…[8] Given the advances in high-field NMR and the development of reverse detection methods, acquisition of NMR data of the so-called low-γ nuclei has been greatly facilitated. This is peculiarly true for 103 Rh NMR where improvement in NMR probe and detection field has allowed a better comprehension [9] of the 103 Rh chemical shifts. A pioneer in this field is von Philipsborn.…”
Section: Introductionmentioning
confidence: 93%
“…Unfortunately, low receptivity, negative magnetogyric ratio and very long relaxation times (>50 s) are major drawbacks. A recent survey of 103 Rh NMR spectroscopy has been published [178], but no studies of biological relevance appear to have been reported.…”
Section: Cobalt and Rhodiummentioning
confidence: 99%
“…This makes it difficult to relate, for example, the geometry around a metal with its chemical shift [13]. It is this local effect that makes it possible to use NMR as a structural characterization tool.…”
Section: Generalmentioning
confidence: 99%
“…For example, the magnitude of the 1 J RhH coupling constant provides information about the degree of s-character of the bond [13]. Both the magnitude of the coupling constant and the multiplicity (which reflects the number of (equivalent) nuclei that couple) are important.…”
Section: Coupling Constantmentioning
confidence: 99%